2007
DOI: 10.1097/gim.0b013e318159a303
|View full text |Cite
|
Sign up to set email alerts
|

Results communication and patient education after screening for possible hemochromatosis and iron overload: experience from the HEIRS Study of a large ethnically and linguistically diverse group

Abstract: ; for the Hemochromatosis and Iron Overload Study Research InvestigatorsPurpose: We assessed the effectiveness of educational interventions for conveying clinical findings and information about hereditary hemochromatosis (HH) and iron overload (IO) to individuals evaluated clinically after initial screening for HH/IO with serum ferritin (SF) concentration, transferrin saturation (TS), and HFE genotyping. Methods: A questionnaire mailed to 2300 cases and controls 1 month after a letter summarizing clinical find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Having a variant genotype and slightly abnormal iron levels was equated with illness by some, comprising an additional source of potential confusion in combined genetic and phenotypic screening. A similar pattern was found among HEIRS study participants who screened positive for HH or IO, and completed a comprehensive clinical exam with genetic counseling and a follow-up letter (Walker et al, 2007).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Having a variant genotype and slightly abnormal iron levels was equated with illness by some, comprising an additional source of potential confusion in combined genetic and phenotypic screening. A similar pattern was found among HEIRS study participants who screened positive for HH or IO, and completed a comprehensive clinical exam with genetic counseling and a follow-up letter (Walker et al, 2007).…”
Section: Discussionsupporting
confidence: 51%
“…Walker et al (2007) found that screen-positive participants from different language=ethnicity groups differed in understanding even after postresults genetic counseling. Non-White and=or nonEnglish-speaking groups had poorer understanding of their genotype and iron level implications.…”
Section: Introductionmentioning
confidence: 97%
“…79 These results may have important implications for screening studies in which information about genotype and phenotype are communicated to participants. A number of factors predicted lower understanding of test results among participants, including lower education levels, older age, and being non-white and/or non-English speaking 80 ; C282Y homozygotes had the best understanding of genetic results. Thus, explaining aberrant TfS and SF test results and genotypes, and communicating recommendations for further evaluation and the need for screening relatives, require culturally appropriate strategies.…”
Section: Social Ethical and Legal Issues (Elsi) Related To Screeninmentioning
confidence: 99%
“…(7) In a previous HEIRS study, only 2.1 percent of those with neither genotypic or phenotypic abnormality incorrectly believed that they had hemochromatosis (with 4.5 percent unsure), suggesting that the risk message was clear for the vast majority. By contrast, 9.7 percent of those with a low-risk gene abnormality and normal iron values (similar to our Group 5) incorrectly believed they had hemochromatosis (with 15.3 percent unsure).…”
Section: Discussionmentioning
confidence: 98%
“…(6) Walker found that, while nearly 90% of participants in the clinical examination phase of HEIRS felt the results letters contained sufficient information, nearly half (47.5%) of the respondents across all genotype/phenotype combinations still had questions after receiving the results. (7)…”
Section: Discussionmentioning
confidence: 99%